AGAMA DALAM PROSES KEBANGKITAN ADAT DI INDONESIA: Studi Masyarakat Rencong Telang Kerinci Jambi - Mahli Zainuddin; Ahmad Norma Permata (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
After the fall of the New Order, Indonesia witnessed a political revival of traditions. Four factors have been identified as that lead to the revival: first, orchestrated campaigns by local and international NGOs to protect traditional communities’ access to lands and natural resources; second, as efforts by local elites to fill the power vacuum after the centralist new order government ended; third, struggles by local groups that suffered marginalization during the previous regime to reclaim their rights; finally, efforts by local groups to adopt alternative social norms in organizing their communities. However, a more detailed description on how these revivals carried out is difficult to find. This article put forward such a description, in the case of the Rencong Telang community in Kerinci, Jambi. After almost two decades of decline, the authority of Adat can finally be restored after the corrupt elites have been replaced. Interestingly, it was personal religiosity that served as the criterion to replace them, while leadership accountability always failed to do so. This finding will also enrich the discussion on the relationship between adat and religion beyond conflict and harmony.Pasca runtuhnya Orde Baru, peran adat mengalami kebangkitan politik di berbagai daerah. Paling tidak ada empat faktor yang dianggap mempengaruhi kebangkitan tersebut: pertama, kampanye LSM internasional yang mendorong hak-hak masyarakat adat; kedua, sebagai upaya mengisi kekosongan otoritas lokal pasca runtuhnya rezim Orde Baru; ketiga, sebagai upaya kelompok minoritas yang merasa tertindas selama Orde Baru; dan terakhir, adat sebagai alternatif membangkitkan idealisme tatanan sosial–namun tidak banyak penjelasan bagaimana proses kebangkitan tersebut terjadi. Kebangkitan otoritas adat di kalangan masyarakat Rencong Telang, Kerinci, Jambi menjadi kasus yang menarik. Setelah hampir dua dekade mengalami kemerosotan–seiring dengan kemerosotan ekonomi yang diiringi perubahan politik akibat desentralisasi–Adat kehilangan otoritasnya karena tokoh adat terjebak pragmatisme politik dan instrumentalisasi adat untuk pragmatisme politik berujung pada saling pecat. Berbagai upaya konsolidasi dilakukan, dan baru berhasil setelah dilakukan penegakan sanksi adat secara tegas. Menariknya, yang menjadi kriteria penegakan sanksi adalah ketaatan beragama. Sehingga agama menjadi kriteria kredibilitas lembaga Adat. Ini sekaligus menjadi tambahan pengayaan bagi kajian relasi adat dan agama yang selama lebih banyak memperdebatkan konflik dan harmoni.